التفاعل بين أنماط تلميحات الفيديو وزمن العرض في بيئة للتدريب المصغر النقال وأثره في تنمية مهارات التصميم التعليمي للفصل المعكوس والاتجاه نحو بيئة التدريب، وخفض العبء المعرفي لدى المعلمين - أبو خطوة، السيد عبدالمولى السيد (الجمعية المصرية للكمبيوتر التعليمي, 2020)
يهدف البحث الحالي إلى الكشف عن التفاعل بين أنماط تلميحات الفيديو (السمعية، البصرية، السمعبصرية)، وزمن عرض الفيديو (قصير، طويل) في بيئة للتدريب المصغر النقال، وقياس أثره في تنمية الجانبي المعرفي، والأدائي لمهارات التصميم التعليمي للفصل المعكوس، والاتجاه نحو بيئة التدريب، وخفض العبء المعرفي لدى عينة من المعلمين، وأعد الباحث (6) معالجات تجريبية لأنماط تلميحات الفيديو، وزمن عرض الفيديو، واستخدم المنهج الوصفي، والمنهج التجريبي، والتصميم التجريبي العاملي 3X2، وتكونت عينة البحث من (90) معلماً ومعلمة تم اختيارهم من ثماني إدارات تعليمية بمحافظة الإسكندرية، وقسموا إلى ست مجموعات بلغ عدد كل منها (15) معلماً ومعلمة، وأعدت أدوات البحث المتمثلة في: اختبار تحصيل الجانب المعرفي، واختبار الجانب الأدائي لمهارات التصميم التعليمي للفصل المعكوس، ومقياس الاتجاه نحو بيئة التدريب، ومقياس العبء المعرفي. وقد أظهرت نتائج البحث وجود فروق ذات دلالة إحصائية عند مستوى > (0.05) بين متوسطات درجات مجموعات البحث التجريبية في تحصيل الجانب المعرفي، والجانب الأدائي لمهارات التصميم التعليمي للفصل المعكوس، وخفض العبء المعرفي لصالح التلميحات السمعبصرية، وصالح زمن العرض القصير (من 2-4 دقائق)، كما كشفت النتائج عدم وجود أثر للتفاعل بين أنماط تلميحات الفيديو (السمعية- البصرية- السمعبصرية) وزمن عرض الفيديو (قصير- طويل) في بيئة التدريب المصغر النقال، في جميع المتغيرات التابعة لهذا البحث؛ وأوصى البحث باستخدام التلميحات السمعبصرية، وزمن الفيديو القصير (من 2-4 دقائق) في بيئات التدريب المصغر النقال؛ مما يحقق نتائج أفضل في التدريب، ويحسن اتجاهات المعلمين نحوه، كما أوصى البحث باستخدام التدريب المصغر النقال في تنمية معارفة المعلمين ومهاراتهم؛ للتغلب على مشكلات التدريب التقليدي.
The current research aims to uncover the interaction between the patterns of video cues (audio, visual, audiovisual), and video display time (short, long) in a mobile microtraining environment, and to measure its effect on the development of the achievement and the performance aspects of the instructional design skills of the flipped classroom and the attitude towards the micro training environment, and the reduction of the cognitive load of a sample for teachers. The researcher has prepared (6) experimental treatments for video cues patterns and its display time. Moreover, the researcher has used the experimental and the descriptive approach and factorial experimental design 2 × 3. The research sample consists of (90) teachers who were chosen from eight educational administrations in Alexandria Governorate. They were divided into six groups of (15) male and female teachers. The research tools were an achievement test for cognitive aspect, performance test for instructional design skills of flipped classroom, tendency scale towards the training environment and scale for cognitive load. The results of the research have showed that there are statistically significant differences at the level <(0.05) between the mean scores of the experimental research groups regarding the cognitive aspect, and the performance aspect of the instructional design skills for the flipped classroom, and reducing the cognitive load in favor of audiovisual cue and short time display (2-4 minutes) while there were no statistically significant differences of the interaction between video cue patterns (audio- visual- audiovisual) and the display time(short-long) in the micro training environment in all the dependent variables. Therefore, the research recommends using audiovisual cue and short video time (2-4) minutes in the micro mobile training environments. This achieves the best results in training and improves the teachers’ tendencies towards it. The research also recommends using micro mobile training in developing teachers’ knowledge and skills to overcome traditional training programs.
Keywords: التدريبات النقالة -- التعلم الإلكترونى -- تكنولوجيا التعليم -- الاستراتيجيات التعليمية